2016
DOI: 10.1097/qai.0000000000001073
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Morbidity Among Older Children and Adolescents at Diagnosis of HIV Infection

Abstract: Background:Substantial numbers of children with HIV present to health care services in older childhood and adolescence, previously undiagnosed. These “slow-progressors” may experience considerable chronic ill health, which is not well characterized. We investigated the prevalence of chronic morbidity among children aged 6–15 years at diagnosis of HIV infection.Methods:A cross-sectional study was performed at 7 primary care clinics in Harare, Zimbabwe. Children aged 6–15 years who tested HIV positive following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 36 publications
2
74
1
1
Order By: Relevance
“…Over half of older children and adolescents reported at least one chronic respiratory symptom in recent studies from Zimbabwe, Malawi and Kenya [8*,10*,11*,12*,13*,14*]. Chronic cough and sputum production were reported by 21–60% and breathlessness by 12–18%, but wheezing was uncommon [8*,10*,11*,12*,13*,14*,15*].…”
Section: Spectrum Of Chronic Lung Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Over half of older children and adolescents reported at least one chronic respiratory symptom in recent studies from Zimbabwe, Malawi and Kenya [8*,10*,11*,12*,13*,14*]. Chronic cough and sputum production were reported by 21–60% and breathlessness by 12–18%, but wheezing was uncommon [8*,10*,11*,12*,13*,14*,15*].…”
Section: Spectrum Of Chronic Lung Diseasementioning
confidence: 99%
“…Over half of older children and adolescents reported at least one chronic respiratory symptom in recent studies from Zimbabwe, Malawi and Kenya [8*,10*,11*,12*,13*,14*]. Chronic cough and sputum production were reported by 21–60% and breathlessness by 12–18%, but wheezing was uncommon [8*,10*,11*,12*,13*,14*,15*]. The prevalence of tachypnoea is difficult to quantify as definitions vary between studies, but elevated respiratory rates are common [8*,9*,10*,11*, 15*].…”
Section: Spectrum Of Chronic Lung Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recent studies in Southern Africa have demonstrated that about 30% of African HIV-infected older children have chronic respiratory symptoms, classically a chronic cough [often leading to presumptive treatment for tuberculosis (TB)] and reduced exercise tolerance [3,4]. In these studies, even participants with pronounced respiratory impairment looked well at rest, not all had cough, and plain radiological abnormalities were subtle and not consistent with LIP [9].…”
Section: Introductionmentioning
confidence: 99%